Trends in HIV-related knowledge, behaviors and determinants of HIV testing among adolescent women aged 15–24 in Nigeria - Okoro Lenz Nwachinemere; Simon Nyegenye; Aaron Mwesigwa; Naya Gadzama Bulus; Jonathan Mawutor Gmanyami; Kaweesi Abdulrahim Mukisa; Isaac Isiko (Tropical Medicine and Health)
Abstract Background HIV remains one of the major global public health challenges, having claimed over 36 million lives so far, especially in sub-Saharan African countries like Nigeria. This study aimed to look into the trends in HIV-related knowledge, behavior and testing among young women in Nigeria. Methods This study used data extracted from women aged 15–24 years who indicated that they had undergone HIV testing from the Nigeria Multiple Indicator Cluster Surveys (MICS) for 2007, 2011, and 2016. Across these surveys, similar sampling designs were applied, using a two-stage cluster sampling to generate a nationally representative sample of households. In the first stage, clusters were selected using the most recent available census from sampling frames. In the second stage, households were selected from each cluster. There was stratification of urban and rural for the different sampled clusters. The analysis was performed using STATA 17 software. Results Northwest and South-South geopolitical zones, rural residential status and good knowledge about HIV were significantly associated with HIV testing. From 2011 to 2016, young women with primary education were significantly associated with reduced odds of HIV testing compared to those with at least secondary education. Young women with good behavior towards HIV prevention were significantly associated with higher odds of HIV testing, ranging from 1.7 times higher in 2011 to 1.8 times higher in 2016 compared with young women with poor behavior. Conclusion By prioritizing education, integrating HIV education and testing into school-based programs, and increasing access to healthcare services in rural areas, we can empower adolescents to make informed decisions about their health and reduce the spread of HIV.